UJI AKTIVITAS ANTIKOLESTEROL EKSTRAK DAUN KETEPENG CINA (Cassia alata L.) TERHADAP PENURUNAN KADAR KOLESTEROL MENCIT PUTIH JANTAN (Mus musculus L.) - Khoirila, Nisa; Walid, Muhammad (JIFI (Jurnal Ilmiah Farmasi Imelda), 2024)
High levels of cholesterol in the blood can increase the risk of hypertension, coronary heart disease (CHD), stroke, peripheral artery disease (PAD), and type 2 diabetes. One potential plant for traditional medicine to lower cholesterol levels is Cassia alata L. Cassia alata L. is known to contain flavonoid compounds, suspected to act as cholesterol-lowering agents in the body. This study aimed to determine the anti-cholesterol activity of Cassia alata L. in reducing cholesterol levels in male white mice (Mus musculus L.). The research employed an experimental design, utilizing the maceration method with 96% ethanol as the solvent for extraction. Male white mice aged 3-4 months, weighing 20-30 grams, were used as test subjects. The first group served as the positive control using simvastatin suspension, the second group as the negative control using 0.5% Na CMC solution, the third group received Cassia alata L. extract at a concentration of F1 (10%), F2 (20%), F3 (30%). Data analysis was performed using One Way Anova. The results of the One-way Anova test obtained F count 31.192 > F table 3.48 and sig. value of 0.000 <0.05, so Ho is rejected and Ha is accepted which can be concluded that there is an effect of anticholesterol activity on Cassia alata L. extract. concentration of 10%, 20%, and 30%. Then in the Post Hoc Test using LSD, K (+) showed the same results as F3 (30%) with a significant value of 0.54 so that p>0.05 which showed no significant difference in anticholesterol effectiveness between K (+) and F3 (30%). The results revealed that Cassia alata L. extract at concentrations of 10%, 20%, and 30% exhibited activity in reducing cholesterol levels, which is F3 (30%) demonstrating the most significant cholesterol-lowering effect. This is attributed to the presence of flavonoid compounds in the Cassia alata L. extract.